Ferric citrate for the treatment of hyperphosphatemia and iron deficiency anaemia in patients with NDD-CKD: a systematic review and meta-analysis - Ding, Xueying; Sun, Shujie; Zhang, Jinjin; Zhao, Huifang; Lun, Fenglan; Liu, Xuemin; Zhen, Yiwan; Dong, Jinping; Wu, Jingliang (Frontiers in Pharmacology, 2024)
The application of ferric citrate therapy has yielded unexpected benefits in recent years for CKD patients suffering from hyperphosphatemia and iron deficiency -anaemia. Despite this, earlier research on the impact of ferric citrate on NDD-CKD has been contentious.The goal of the meta-analysis is to evaluate the evidence regarding the advantages and dangers of ferric citrate for the treatment of hyperphosphatemia and iron deficiency anaemia in NDD-CKD patients.Methods: Between the start of the study and June 2022, we searched PubMed, Embase, Cochrane, EBSCO, Scopus, Web of Science, Wan Fang Data, CNKI, and VIP databases for randomised controlled trials of iron citrate for hyperphosphatemia and anaemia in patients with NDD-CKD. For binary categorical data, risk ratios (OR) were employed, and for continuous variables, weighted mean differences (WMD).The effect sizes for both count and measurement data were expressed using 95% confidence intervals (CI).The meta-analysis includes eight trials with a total of 1281 NDD-CKD patients. The phosphorus-lowering effect of ferric citrate was greater compared to the control group (WMD, -0.55, 95% CI, -0.81 to -0.28; I 2 = 86%, P < 0.001). Calcium (WMD, 0.092; 95% CI, -0.051 to 0.234; P > 0.05; I 2 = 61.9%), PTH (WMD, -0.10; 95% CI, -0.44 to 0.23; I 2 = 75%, P > 0.05) and iFGF23 (WMD, -7.62; 95% CI, -21.18 to 5.94; I 2 = 20%, P > 0.05) levels were not statistically different after ferric citrate treatment compared to control treatment. Furthermore, ferric citrate increased iron reserves and haemoglobin. The ferric citrate group had considerably greater levels than the controls. Ferric citrate, on the other hand, may raise the risk of constipation, diarrhoea, and nausea.This meta-analysis found that ferric citrate had a beneficial effect in the treatment of NDD-CKD, particularly in reducing blood phosphorus levels when compared to a control intervention. It also shown that ferric citrate has a favourable effect on iron intake and anaemia management. In terms of safety, ferric citrate may 3 / 30 increase the likelihood of gastrointestinal side effects.